The role of synaptic biomarkers in the spectrum of neurodegenerative diseases. (2nd August 2020) - Mazzucchi, Sonia; Palermo, Giovanni; Campese, Nicole; Galgani, Alessandro; Della Vecchia, Alessandra; Vergallo, Andrea; Siciliano, Gabriele; Ceravolo, Roberto; Hampel, Harald; Baldacci, Filippo
ABSTRACT: Introduction: The quest for reliable fluid biomarkers tracking synaptic disruption is supported by the evidence of a tight association between synaptic density and cognitive performance in neurodegenerative diseases (NDD), especially Alzheimer's disease (AD). Areas covered: Neurogranin (Ng) is a post-synaptic protein largely expressed in neurons involved in the memory networks. Currently, Ng measured in CSF is the most promising synaptic biomarker. Several studies show Ng elevated in AD dementia with a hippocampal phenotype as well as in MCI individuals who progress to AD. Ng concentrations are also increased in Creutzfeldt Jacob Disease where widespread and massive synaptic disintegration takes place. Ng does not discriminate Parkinson's disease from atypical parkinsonisms, nor is it altered in Huntington disease. CSF synaptosomal-associated protein 25 (SNAP-25) and synaptotagmin‐1 (SYT-1) are emerging candidates. Expert opinion: CSF Ng revealed a role as a diagnostic and prognostic biomarker in NDD. Ng increase seems to be very specific for typical AD phenotype, probably for a prevalent hippocampal involvement. Synaptic biomarkers may serve different context-of-use in AD and other NDD including prognosis, diagnosis, and tracking synaptic damage – a critical pathophysiological mechanism in NDD – thus representing reliable tools for a precision medicine-oriented approach to NDD.